The Sensitivity Profile of Santri Towards Energy Saving Behavior (Case Study at the Pondok Pesantren Putri Jagad 'Alimussirry) - Rofi'ah, Alfiatur; Handriyan, Aris (http://jagadalimussirry.com/, 2020)
Abstract. Pondok Pesantren Putri Jagad 'Alimussirry is one of the Islamic boarding schools in the city of Surabaya. The majority of those living in this pesantren are students and students who are actively studying. Santri (Ø§Ù„Ø³Ù†ØªØ±ÙŠ) based on the review of their actions are